Avaliação hemodinâmica, estresse, perfil metabólico e balanço autonômico em profissionais bombeiros militares - Spacassassi, Fabio (2015)
A day-to-day activity as a professional firefighter leads you to a physical and psychological risk constantly. These stressful situations may cause to this professional a physiological disorder that chronically can lead to the onset of other cardiovascular diseases. Our proposal was the identification of the type of stress and its symptoms, and the hemodynamic and metabolic alterations that can effect from daily routine experiences throughout its operational career. The study compared a group of firefighters GB (n = 52), working in the operational business for over 5 years, with a control group, CO (n = 52), representing the general population. These two groups were composed by healthy volunteers who concluded a clinical evaluation before applying the tests. Data were matched by age, sex and race and calculated by weight, height, body mass index and anthropometric measurements of neck circumference, waist circumference, hip circumference and waist-hip ratio. The autonomic evaluation was performed by the frequency meter Polar device (model RS800) through the heart rate variability evaluated in time (SDNN, RMSSD and variance) and frequency (HF, LF and HF / LF) domain. The stress rate was performed by psychosocial adjustment scale Holmes-Rahe via a score that classifies the probability of potential professional illness. The hemodynamic evaluation was performed by non-invasive indirect technique with Hypertension Diagnosis Incorporation (H.D.I), with the variables systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate (HR), pulse pressure, cardiac output (CO), impedance, systemic vascular resistance (SVR) and elasticity index of large and small arteries. Commercial kits were used for biochemical data (total cholesterol, triglycerides, HDL-C, LDL-C, creatinine, uric acid, urea and glucose). It was verified that the autonomic assessment indexes SDNN (39.5 ± 3.0 ms), VARR (1734.4 ± 238.9 ms2) and RMSSD (23.5 ± 2.4 ms) were significantly lower (p<0.05) in GB than CO: SDNN (59.9 ± 5.6 ms), VARR (4108.3 ± 752.4 ms2), RMSSD (45.1 ± 7.8 ms), and higher for GB LF/HF (3.6 ± 0.4) than CO (2.3 ± 0.2). For the stress perception there was no difference between groups. The Hemodynamic data was significantly higher (p<0.05) for the GB with SBP (131.1 ± 1.8 seg/cm5), FC (81.2 ± 1.6 bpm), SVR (1234 ± 23.8 seg/cm5), impedance (125.0 ± 5.9 seg/cm5) and DC (5.7 ± 0.09 L/min ) in relation to CO which showed systolic blood pressure (125 ± 16.8 mmhg), FC (71.1 ± 1.4 bpm), SVR (1141 ± 32.5 seg/cm5), impedance (104.5 ± 3.9 seg/cm5), DC (5.0 ± 0.1 L/min) and biochemistry profile with significantly higher (p<0.05) values for the GB in CT (203 ± 4.9 mg/dL), HDL (47.6 ± 1.4 mg/dL), creatinine (1.1 ± 0.09 mg/dL) and glucose (99.0 ± 2.4 mg/dL) than CO with CT (163.5 ± 4.5 mg/dL), HDL (39.8 ± 1.5 mg/dL), creatinine (1,0 ± 0,02 mg/dL) and glucose (89,8 ± 1,1 mg/dL). Through the results it was concluded that the autonomic balance was worst in the firefighter than in control group. The results of anthropometric, hemodynamic and metabolic profile also were worst in the firefighters. It suggests a possible susceptibility for cardiovascular disease development in firefighters.